The complete mitochondrial genome of the Aral barbel Luciobarbus brachycephalus (Cypriniformes: Cyprinidae: Barbinae) - Haifeng Jiang; Longwu Geng; Jian Yang; Guangxiang Tong; Chenyu Li; Wei Xu (Mitochondrial DNA. Part B. Resources, 2019)
The Aral barbel (Luciobarbus brachycephalus) is an important commercial species in Aral sea basin and its population is decreasing rapidly. However, the genetic resource available for this species as well as other barbels in barbinae is limited. In this study, we described the complete mitochondrial genome of L. brachycephalus. The mitochondrial genome is 16,603 bp in length containing 13 protein-coding genes (PCGs), two ribosomal RNAs, 22 tRNAs and a control region. The overall base composition of L. brachycephalus mtDNA is: 31.2% for A, 27.8% for C, 16.5% for G, 24.4% for T.